Índices notícia-morbidade e notícia-morte: relação entre o perfil de morbimortalidade da população e a divulgação midiática no Estado do Espírito Santo, Brasil, 2011-2012 (Brazilian Journal of Health Research, 2019)
Morbidity news and death-news Indices: relationship between the morbidity and mortality profile of the population and information in the media in Espírito Santo State, Brazil, 2011-2012